IgG mediated suppression of immunological memory - Petersson, Jennifer (2015)
Apart from recognizing and neutralizing threats, antibodies also have the ability to regulate immune responses against their specific antigen. IgG administered together with erythrocytes is well known to induce >99% suppression. This has been used to prevent haemolytic disease in new-borns since the 1960's, but the mechanism behind it is still not completely understood. The effect on the primary response is well established, but its influence on induction of immunological memory is still heavily debated. In this study adoptive cell transfer of splenocytes to irradiated mice was used to survey the effect IgG has on induction of immunological memory without disturbance from the primary IgG response. Alongside this, an in situ boost experiment with two different priming doses was performed and antibody levels in serum detected using ELISA. When mice were primed with 10μg IgG-anti-SRBC (Sheep red blood cells) + 5x106 SRBC, a 10-fold IgG suppression of memory was observed when using adoptive transfer and complete suppression of induction of immunological memory was seen in in situ boosted mice when primed with a 10 times higher antigen dose. A comparison to the primary IgG response in all experiments showed that, to allow for complete suppression of memory induction, there must be a complete suppression of the primary response as well. This brings us to the conclusion that the induction of the memory response depends on the primary response.